Abnormal overexpression of SoxD enhances melanin synthesis in the Ursa mutant of Bombyx mori. (October 2022) - Wang, Niannian; Zhang, Yinxia; Li, Wei; Peng, Zhangchuan; Pan, Huan; Li, Shan; Cheng, Tingcai; Liu, Chun
Abstract: The pigment and structural color of insects play crucial roles in body protection, ecological adaptation, and signal communication. Epidermal melanization is a common and main coloring pattern, which results in broad phenotypic diversity. Melanin is one of the compounds contributing to dark brown-black pigmentation, which is synthesized from dopamine and tyrosine by the melanin metabolism pathway. The Ursa mutant of the silkworm Bombyx mori is a body-color mutant characterized by excessive melanin pigmentation in the larval epidermis. However, the exact gene responsible for this phenotype remains unclear. Here, we performed positional cloning of the gene responsible for Ursa, which was mapped to an 83-kb region on chromosome 14. The genomic region contains a protein-coding gene encoding a transcription factor, which was designated BmSoxD . The mutation site was determined by analysis of nucleotide sequences of the genomic region corresponding to BmSoxD, which identified a 449-bp transposable sequence similar to that of the B. mori transposon Helitron inserted into the sixth intron. BmSoxD was dramatically overexpressed in the epidermis of Ursa at the end of the molting stage compared with that of wild-type B. mori . Overexpression of BmSoxD led to upregulation of genes involved in the melanin metabolism pathway, whereas knocking down BmSoxD via small interfering RNAs blocked melanin pigment production in the larval epidermis. These data indicate that the mutation in BmSoxD is responsible for the Ursa mutant phenotype. We propose that the transposable sequence insertion causes abnormal overexpression of BmSoxD at the molting stage in the Ursa mutant, resulting in excessive melanin synthesis and its accumulation in epidermal cells. Graphical abstract: Image 1 Highlights: BmSoxD is the candidate gene of the Ursa mutant. BmSoxD is dramatically overexpressed in the Ursa epidermis. BmSoxD regulates melanin synthesis in the epidermis.